Conjugated Coordination Polymer as a New Platform for Efficient and Selective Electroreduction of Nitrate into Ammonia - Zhang, Yizhe; Zheng, Hui; Zhou, Kangjie; Ye, Jinyu; Chu, Kaibin; Zhou, Zhiyou; Zhang, Longsheng; Liu, Tianxi (Advanced materials (Weinheim), 2023)
Electroreduction of nitrate into ammonia (NRA) provides a sustainable route to convert the widespread nitrate pollutants into high‐value‐added products under ambient conditions, which unfortunately suffers from unsatisfactory selectivity due to the competitive hydrogen evolution reaction (HER). Previous strategies of modifying the metal sites of catalysts often met a dilemma for simultaneously promoting activity and selectivity toward NRA. Here, a general strategy is reported to enable an efficient and selective NRA process through coordination modulation of single‐atom catalysts to tailor the local proton concentration at the catalyst surface. By contrast, two analogous Ni‐single‐atom enriched conjugated coordination polymers (NiO4‐CCP and NiN4‐CCP) with different coordination motifs are investigated for the proof‐of‐concept study. The NiO4‐CCP catalyst exhibits an ammonia yield rate as high as 1.83 mmol h−1 mg−1 with a Faradaic efficiency of 94.7% under a current density of 125 mA cm−2, outperforming the NiN4‐CCP catalyst. These experimental and theoretical studies both suggest that the strategy of coordination modulation can not only accelerate the NRA by adjusting the adsorption energies of NRA intermediates on the metal sites but also inhibit the HER through regulating the proton migration with contributions from the metal‐hydrated cations adsorbed at the catalyst surface, thus achieving simultaneous enhancement of NRA selectivity and activity. A general strategy for simultaneous enhancement of activity and selectivity toward nitrate electroreduction into ammonia (NRA) is demonstrated by utilizing Ni‐based conjugated coordination polymer catalysts for the proof‐of‐concept study. Coordination modulation can tailor their electrostatic attractions with the metal‐hydrated cations that can regulate proton migration at the catalyst surface, promoting the NRA and inhibiting the competitive hydrogen evolution reaction (HER).